Fatty Acids of Erythrocyte Membranes and Blood Serum in Differential Diagnosis of Inflammatory Bowel Diseases - M. V. Kruchinina; I. O. Svetlova; M. F. Osipenko; N. V. Abaltusova; A. A. Gromov; M. V. Shashkov; A. S. Sokolova; I. N. Yakovina; A. V. Borisova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to study fatty acid levels in erythrocyte membranes (RBC) and blood serum (BS) in patients with inflammatory bowel diseases (IBDs) to develop differential diagnostic models including fatty acids as biomarkers to distinguish between nosological entities of IBDs (ulcerative colitis — UC, Crohn's disease — CD, unclassified colitis — UCC).Materials and methods. We examined 110 patients (mean age 37,7 ± 12,1 years) with IBDs and 53 healthy patients in control group (43,3 ± 11,7 years). The IBDs group included 50 patients with UC, 41 patients with CD, 19 patients with UCC. An exacerbation of the disease was revealed in 42 patients (84 %) with UC, 34 patients with CD (82.9 %) and 11 people with UCC (57.9 %). The study of fatty acids (FA) composition of RBC membranes and BS was carried out using GC/MS system based on three Agilent 7000B quadrupoles (USA).Results. The most significant for distinguishing active UC from CD exacerbation were serum levels of elaidin (p = 0.0006); docosatetraenoic (n-6) (p = 0.004); docodienic (n-6) (p = 0.009); omega-3/omega-6 ratio (p = 0.02); docosapentaenoic (n-3) (p = 0.03); the sum of eicosapentaenoic and docosahexaenoic (p = 0.03), as well as the content of RBC lauric FA (p = 0.04) (AUC — 0.89, sensitivity — 0.91, specificity — 0.89, diagnostic accuracy — 0.91). To distinguish active UC from the same of UCC, the following serum FA were found to be significant: alpha-linolenic; saturated (pentadecanoic, palmitic, stearic, arachidic); monounsaturated (palmitoleic, oleic); omega-6 (hexadecadienic, arachidonic) (p = 0.00000011—0.03300000) (AUC — 0.995, sensitivity — 0.98, specificity — 0.96, diagnostic accuracy — 0.97). The most significant in distinguishing patients with active CD from UCC exacerbation were levels of the following FA: alpha-linolenic; palmitoleic; oleic; the amount of saturated fatty acids (SFA); total unsaturated fatty acids (UFA); stearic; monounsaturated fatty acids (MUFA) amount; SFA/UFA; SFA/PUFA (polyunsaturated fatty acids); linoleic; total PUFA n6; lauric; arachidic acid (p = 0.0000000017–0.030000000) (AUC — 0.914, sensitivity — 0.90, specificity — 0.87, diagnostic accuracy — 0.91).Conclusion. The study of FA levels in groups with different nosological forms of IBDs using complex statistical analysis, including machine learning methods, made it possible to create diagnostic models that differentiate CD, UC and UCC in the acute stage with high accuracy. The proposed approach is promising for the purposes of differential diagnosis of nosological forms of IBDs.